An analysis of the lesson plan contents and written test design that affected intensive advanced English I students’ outcomes of the major Licenciatura en Idioma Ingles opcion Enseñanza at the University of El Salvador, Western Multidisciplinary Campus, semester ii, 2018 - Henríquez León, Kelly Stephanie; Martínez Valiente, Evelyn Noemí; Rosales Jiménez, Zuleyma Saraí (2024)
This investigation aims to identify if the written test design affected Intensive Advanced English I students’ outcomes; that is why, researchers decided to make a documentary analysis called “An Analysis Of The Lesson Plan Contents And Written Test Design That Affected Intensive Advanced English I Students’ Outcomes Of The Major Licenciatura En Idioma Ingles Opcion Enseñanza At The University Of El Salvador, Western Multidisciplinary Campus, Semester II, 2018.